Weighted Local BMO Spaces and the Local Hardy-Littlewood Maximal Operator - Chicco Ruiz, Anibal Leonardo (2011)
The purpose of this work is to investigate the behavior of the Local MaximalOperator on appropriate weighted BMO spaces. We believe that ourresult (see theorem below) is new even in the unweighted case.